Uji Performa Trafo E-I dengan Variasi Rapat Fluks pada Sumber Tegangan Non-Sinusoidal - Slamet Nurhadi; Anang Dasa Nofvowan; Ika Noer Syamsiana; Yanik Lailinas Sakinah; Masramdhani Saputra; Mochammad Nur Rochman (Politeknik Negeri Malang, 2023)
In the industrial field, transformers are used as a step-up voltage and are used as a step-down level. In a loaded transformer, the power that comes out of the transformer (transformer output power) is not always 100% because there are losses when channeling to the load. Both losses caused by current flowing in the copper wire, losses caused by alternating flux in the iron core, and losses caused by Eddy current in the iron core which result in the outgoing power (output power) from the transformer to the load is not the same as the incoming power (input power) to the transformer. This is known as the efficiency of the transformer. From these problems, the solution offered is to design and implement a transformer using an EI-shaped iron core which is arranged alternately which aims to prevent the occurrence of Eddy Current what happens in the coresolid by applying to the inverter. From the test results of the transformer, it can be concluded that the difference in flux density in the transformer when it is loaded will affect efficiency. The smaller the flux density of the transformer, the better the efficiency, while the greater the flux density of the transformer, the lower the efficiency.